Physical parameterisation of 3C-Silicon Carbide (SiC) with scope to evaluate the suitability of the material for power diodes as an alternative to 4H-SiC - Arvanitopoulos, A.; Lophitis, Neophytos; Perkins, Samuel; Gyftakis, K. N.; Belanche Guadas, M.; Antoniou, Marina (My University, 2017)
Major recent developments in growth expertise related to the cubic polytype of Silicon Carbide, the 3C-SiC, coupled with its remarkable physical properties and the low fabrication cost, suggest that within the next five years, 3C-SiC devices can become a commercial reality. It is therefore important to develop Finite Element Method (FEM) techniques and models for accurate device simulation. Furthermore, it is also needed to perform an exhaustive simulation investigation with scope to identify which family of devices, which voltage class and for which applications this polytype is suited. In this paper, we present a complete set of physical models and material parameters for bulk 3C-SiC aiming Technology Computer Aided Design (TCAD) tools. These are compared with those of 4H-SiC, the most well developed polytype of SiC. Thereafter, the newly developed material parameters are used to assess 3C- and 4H-SiC vertical power diodes, P-i-N and Schottky Barrier Diodes (SBDs), to create trade-off maps relating the on-state voltage drop and the blocking capability. Depending on the operation requirements imposed by the application, the developed trade-off maps set the boundary of the realm for those two polytypes. It also allows us to predict which applications will benefit from an electrically graded 3C-SiC power diodes.
Keywords: 3C-SiC; FEM simulations; material parameters; P-i-N; SBD; semiconductor physics; TCAD model; vertical diodes